The Profiling of PASS Cognitive Processing among Children with Learning Difficulties - Boon Keat, Ooi; Leena Rajaratnam, Monica; Salis Yuniardi, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed at exploring the profiles of PASS cognitive processes for children with learning difficulties among primary school children. The four cognitive processes, which are Planning, Attention, Simultaneous, and Successive (PASS), operate mental processing in most of the academic tasks. This study included 279 children with LD among those who follow the Literacy and Numeracy Screening System (LINUS) program in schools. There were 12 schools from 4 clusters of peninsular Malaysia, which are the northern, southern, central, and east coast of Malaysia, selected in this study. The participants were identified through LINUS achievement and recommendation of remedial class teachers according to the criteria of learning difficulties. The identified children were administered the CAS-2 as the instrument to measure general cognitive ability with specific PASS cognitive processes. The individually administered test was conducted on a one-on-one basis by eight research assistants. The findings of the study showed 22.6% of the children who were categorized in the LD group had average and above-average cognitive ability levels. Children with LD showed poor processing in all aspects of cognitive processes, especially simultaneous processing. The policymakers, school administrators, and teachers need to take individual differences into consideration while designing the curriculum, especially for children with LD. Through identification of general cognitive ability level and specific cognitive processing of cognitive ability components, we would be able to help the children more objectively and meaningfully.